Influenza a (h1n1) was not associated with obesity in pregnant women living in toluca, méxico (2011)
Objective The aim was to verify whether being overweight could have played a critical role in cases of mortality caused by influenza A (H1N1) in pregnant women. This virus’  prevalence was also analyzed among people suffering from acute respiratory disease being attended at the state of Mexico’s Autonomous University’s medical research centre.Methods The clinical files of women having influenza A (H1N1) attending the Monica Pretelini maternal-perinatal hospital’s (HMPMP) intensive care unit in Toluca, Mexico, were reviewed. According to international recommendations, clinical detection of possible new cases of this disease was kept an open as a second step.Results Five women suffering influenza A (H1N1) was attended at HMPMP’s intensive care unit during 2009; only one survived. No differences in body mass index were found when comparing the anthropometric characteristics to another group of women affected by acute respiratory diseases; in fact, this parameter was below the limits for being overweight in both cases. No new case of influenza A (H1N1) was found after the first eight months of 2010.Discussion It could not be verified whether being overweight was a factor of higher mortality due to influenza A (H1N1) amongst pregnant women in the state of Mexico. The key to better survival for pregnant women hospitalized with influenza A (H1N1) seemed to be early treatment with oseltamivir. The cases decreased dramatically after the severe wave of the new pandemic due to unknown reasons.